Cutaneous Viral Infections Across 2 Anatomic Sites Among a Cohort of Patients Undergoing Skin Cancer Screening. (27th September 2018) - Rollison, Dana E; Schell, Michael J; Fenske, Neil A; Cherpelis, Basil; Messina, Jane L; Giuliano, Anna R; Epling-Burnette, Pearlie K; Hampras, Shalaka S; Amorrortu, Rossybelle P; Balliu, Juliana; Vijayan, Laxmi; Naqvi, Syeda Mahrukh Hussnain; et al.
Abstract: Background: Findings from previous studies of cutaneous human papillomavirus (cuHPV) infection and keratinocyte carcinomas have varied due to several factors, including use of different sample types for cuHPV DNA detection. Elucidating the relationship between cuHPV infection in eyebrow hairs (EBHs) and skin swabs (SSWs) is critical for advancing the design of future studies. Methods: DNA corresponding to 46 β-HPV and 52 γ-HPV types was measured in EBHs and SSWs obtained from 370 individuals undergoing routine skin cancer screening examinations. Results: Prevalence of β-HPV/γ-HPV was 92%/84% and 73%/43% in SSWs and EBHs, respectively, with 71%/39% of patients testing positive for β-HPV/γ-HPV in both sample types. Number of cuHPV types detected and degree of infection were correlated across SSWs and EBHs. When the EBH was positive for a given β-HPV/γ-HPV type, the SSW was positive for that same type 81%/72% of the time. Conclusions: Testing SSWs captures more cuHPV infection than EBHs, with EBH infections usually representing a subset of SSW infections. The importance of optimizing sensitivity of cuHPV infection detection using SSWs vs specificity using EBHs (or a combination of the 2) will be ascertained in an ongoing cohort study investigating cuHPV associations with subsequent keratinocyte carcinomas. Abstract : Cutaneous human papillomavirus and polyomavirus infections were present more often in skin swabs than eyebrow hairs, with strong, virus type–specific correlations observed across anatomic sites in terms of prevalence, degree of infection, and number of types.